2018
DOI: 10.1097/meg.0000000000001013
|View full text |Cite
|
Sign up to set email alerts
|

Platelets-to-lymphocyte ratio is a good predictor of liver fibrosis and insulin resistance in hepatitis C virus-related liver disease

Abstract: PLR is useful in distinguishing the patients with significant fibrosis or IR unlike NLR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…There was also only a nominal difference between the respective abilities of LPR and IGPR in predicting fibrosis stages. The similar performance of these factors is likely because of their shared denominator of PLT number in their formulas [15,20,26,27]. In addition, our head-to-head comparison showed that FIB-4 and APRI -the two well-known markers of liver fibrosis [9-12] -did not correlate independently with liver fibrosis stage in our AIH cohort.…”
Section: Discussionmentioning
confidence: 82%
“…There was also only a nominal difference between the respective abilities of LPR and IGPR in predicting fibrosis stages. The similar performance of these factors is likely because of their shared denominator of PLT number in their formulas [15,20,26,27]. In addition, our head-to-head comparison showed that FIB-4 and APRI -the two well-known markers of liver fibrosis [9-12] -did not correlate independently with liver fibrosis stage in our AIH cohort.…”
Section: Discussionmentioning
confidence: 82%
“…The discriminatory potential of a certain test might be influenced by the reference test. We and others used histological grading as reference standard, while some studies use TE as reference for fibrosis staging . Deviations in diagnostic accuracy might also occur due to the type of histologically analyzed specimen, whether a needle biopsy or a surgical specimen is examined.…”
Section: Discussionmentioning
confidence: 99%
“…We and others 28,29 used histological grading as reference standard, while some studies use TE as reference for fibrosis staging. 30 Deviations in diagnostic accuracy might also occur due to the type of histologically analyzed specimen, whether a needle biopsy or a surgical specimen is examined. In our study, we analyzed surgical resected liver specimens and thus probably decreased the sampling error of unevenly distributed diseased liver parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies of these immunologic parameters have been carried out not only for cancer but also for other kinds of disease. Recent studies have shown that these immunologic parameters are also associated with prognosis in cases of atherosclerotic carotid plaques, Guillain‐Barre syndrome, liver fibrosis and hepatitis C virus‐related liver disease …”
Section: Introductionmentioning
confidence: 99%